Radiological features characterising indeterminate testes masses: a systematic review and meta‐analysis. (9th October 2022) - Ager, Michael; Donegan, Sarah; Boeri, Luca; de Castro, Javier Mayor; Donaldson, James F.; Omar, Muhammad Imran; Dimitropoulos, Konstantinos; Tharakan, Tharu; Janisch, Florian; Muilwijk, Tim; Yuan, Cathy; Tudur‐Smith, Catrin; et al.
Abstract : Context: The use of scrotal ultrasonography (SUS) has increased the detection rate of indeterminate testicular masses. Defining radiological characteristics that identify malignancy may reduce the number of men undergoing unnecessary radical orchidectomy. Objective: To define which SUS or scrotal magnetic resonance imaging (MRI) characteristics can predict benign or malignant disease in pre‐ or post‐pubertal males with indeterminate testicular masses. Evidence Acquisition: This systematic review was conducted in accordance with Cochrane Collaboration guidance. Medline, Embase, Cochrane controlled trials and systematic reviews databases were searched from (1970 to 26 March 2021). Benign and malignant masses were classified using the reported reference test: i.e., histopathology, or 12 months progression‐free radiological surveillance. Risk of bias was assessed using the Quality Assessment of Diagnostic Accuracy Studies‐2 tool (QUADAS‐2). Evidence Synthesis: A total of 32 studies were identified, including 1692 masses of which 28 studies and 1550 masses reported SUS features, four studies and 142 masses reported MRI features. Meta‐analysis of different SUS (B‐mode) values in post‐pubertal men demonstrated that a size of ≤0.5 cm had a significantly lower odds ratio (OR) of malignancy compared to masses of >0.5 cm ( P < 0.001). Comparison of masses of 0.6–1.0 cm and masses of >1.5 cm also demonstrated a significantly lower OR of malignancy ( P = 0.04). There was no significant difference between masses of 0.6–1.0 and 1.1–1.5 cm. SUS in post‐pubertal men also had a statistically significantly lower OR of malignancy for heterogenous masses vs homogenous masses ( P = 0.04), hyperechogenic vs hypoechogenic masses ( P < 0.01), normal vs increased enhancement ( P < 0.01), and peripheral vs central vascularity ( P < 0.01), respectively. There were limited data on pre‐pubertal SUS, pre‐pubertal MRI and post‐pubertal MRI. Conclusions: This meta‐analysis identifies radiological characteristics that have a lower OR of malignancy and may be of value in the management of the indeterminate testis mass.